1991
DOI: 10.1038/nbt1291-1356
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Animal Cell Expression Vectors Based on the Semliki Forest Virus Replicon

Abstract: We have developed a novel DNA expression system, based on the Semliki Forest virus (SFV) replicon, which combines a wide choice of animal cell hosts, high efficiency and ease of use. DNA of interest is cloned into SFV plasmid vectors that serve as templates for in vitro synthesis of recombinant RNA. The RNA is transfected with virtually 100% efficiency into animal tissue culture cells by means of electroporation. Within the cell, the recombinant RNA drives its own replication and capping and leads to massive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
808
1
6

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 830 publications
(820 citation statements)
references
References 33 publications
5
808
1
6
Order By: Relevance
“…[15][16][17][18] SFV is a positive-strand RNA virus belonging to the genus Alphaviruses of the family Togaviridae. 19 Alphaviruses replicate in the host cell cytosol without integration of the viral genetic material in the cellular genome.…”
Section: Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18] SFV is a positive-strand RNA virus belonging to the genus Alphaviruses of the family Togaviridae. 19 Alphaviruses replicate in the host cell cytosol without integration of the viral genetic material in the cellular genome.…”
Section: Gene Therapymentioning
confidence: 99%
“…To permit insertion of heterologous genes, the subgenomic region of the SFV genome, encoding the viral structural proteins, has been deleted from pSP6-SFV4 and replaced by a polylinker site to produce the vector pSFV1. 16 This vector retains the nonstructural region of the viral genome encoding the RNA replicase, thus preserving the self-replicating ability of the SFV replicon. Insertion of a heterologous gene in the polylinker site of SFV1 now allows in vitro production of RNA transcripts containing the foreign gene in the context of the SFV replicon.…”
Section: Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that recombinant RNA vectors based on SFV were transfected with high efficiency into animal tissue culture cells by means of electroporation. 4 Although this system can be used, the preparation of capped RNA vectors by in vitro transcription is necessary before transfection and the RNA molecules are unstable in general. Therefore, it is of great use to construct a DNA vector based on self-amplifying systems of SFV, especially in consideration of in vivo expression.…”
mentioning
confidence: 99%
“…Some of these self-amplifying systems use RNA genomes of alphaviruses, such as Sindbis virus [1][2][3] and Semliki Forest virus (SFV). 4,5 SFV, a member of the Alphavirus genus, is a smallenveloped virus with a single-stranded RNA genome of positive polarity. The 5′ two-thirds of the viral genome encode nonstructural (replication) proteins (nsPs1-4) and the 3′ one-third encodes structural proteins.…”
mentioning
confidence: 99%